PENGOLAHAN COOKIES KAMBAMBANG DENGAN PEMANFAATAN TEPUNG HATI AYAM DAN DAUN KELOR DAN PENGARUHNYA TERHADAP ORGANOLEPTIK PRODUK: Processing kambambang cookies with the addition of chicken liver flour and moringa laeves and their effect on the product’s organoleptic properties - Ina Kaita Niwa niwa; Yessy Tamu ina (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2026)
This study aimed to analyze  the effect of fortification of chicken liver flour and moringa leaf flour (moringa oleifera) on the chemical and organoleptic characteristic of kambambang cookies using a Completely Randomized Design (4 treatments; 5 replicatons). The results showed a water content of 4,36-6,17% with a significant difference (P<0,05). Where P4 (3,36%) met the SNI standrd (<5%), while the pH of 5,49-5,76 was not signifivantly different (p>0.05). protein content ranged from 1,68-2,14% with the highest values in P4 (2,14%) and the lowest in P3 (1,68%), indicating a non-linear increase due to the interaction of the ingredient components. Organoleptic tests showed that taste and preference were significantly different (p<0,05), while color and P4 the highest taste score (2.70). it was concluded that fortification had a significant effect on air content and some sensory attributes, but was not yet able to increase protein according to SNI standards, so formulation optimization was needed to balcance nutritional value and consumer acceptance.